Parenteral supplementation of copper and its relationship with fertility rates in cattle in regions with high levels of molybdenum in Colombian Magdalena Medio - Hernandez-Arroyave, Walter; Eduardo Ocampo-Ortiz, Pablo; Mauricio Montoya-Florez, Luis [UNESP]; Jairo Bustamante-Cano, John (Univ Caldas, 2016)
The hypocuprosis in cattle at the reproductive level, causes delay in the uterine involution, abortions, repetition of services, silent heats and delay in the onset of puberty; the objective of this research was to evaluate the effect of the application of copper on ovarian activity in cattle with hypocuprosis. A group of 212 Cebu-Brahman adult females, clinically healthy and with low reproductive activity was selected for the study. Cows were subjected to a gynecological and ultrasonography test, and then, 106 cows of the treatment group, received 10 mL/animal of calcium cupric edetate at 7.5% subcutaneously. Copper (Cu) levels in blood before and after therapy, and Cu and molybdenum (Mo) in forage collected during periods of rain and drought were measured by atomic absorption spectrophotometry. The data analysis were performed through descriptive statistics and parametric tests. Cu and Mo values in pastures, ranged from 5 to 7 ppm and 20 to 100 ppm respectively; at the pre-treatment blood levels, Cu concentration was low (0.17 +/- 0.009 mg/dl). A noticeable reduction in the size of the cervix and ovaries could be detected during gynecological evaluation, in the ovaries, 40% presented multiple follicles in its early stages. The pregnancy rate was 6%. The micromineral blood levels increased post-treatment (0.66 +/- 0.1 mg/dl), a high pregnancy rate (73%) and a decrease in the number of open days was achieved. It is concluded that ovarian activity in cows in areas with high concentrations of molybdenum remains depressed and corrective treatment with a single dose of copper subcutaneously improves their activity. It is recommended that future research is carried out where the effect of periodic doses of Cu can be evaluated.
Keywords: abortion; copper; molybdenum; spectrophotometry